A novel immune competent murine hypertrophic scar contracture model: A tool to elucidate disease mechanism and develop new therapies. Issue 6 (8th January 2015) - Ibrahim, Mohamed Magdy; Bond, Jennifer; Bergeron, Andrew; Miller, Kyle J.; Ehanire, Tosan; Quiles, Carlos; Lorden, Elizabeth R.; Medina, Manuel A.; Fisher, Mark; Klitzman, Bruce; Selim, M. Angelica; Leong, Kam W.; et al.
Abstract Hypertrophic scar (HSc) contraction following burn injury causes contractures. Contractures are painful and disfiguring. Current therapies are marginally effective. To study pathogenesis and develop new therapies, a murine model is needed. We have created a validated immune‐competent murine HSc model. A third‐degree burn was created on dorsum of C57BL/6 mice. Three days postburn, tissue was excised and grafted with ear skin. Graft contraction was analyzed and tissue harvested on different time points. Outcomes were compared with human condition to validate the model. To confirm graft survival, green fluorescent protein (GFP) mice were used, and histologic analysis was performed to differentiate between ear and back skin. Role of panniculus carnosus in contraction was analyzed. Cellularity was assessed with 4′, 6‐diamidino‐2‐phenylindole. Collagen maturation was assessed with Picro‐sirius red. Mast cells were stained with Toluidine blue. Macrophages were detected with F4/80 immune. Vascularity was assessed with CD31 immune. RNA for contractile proteins was detected by quantitative real‐time polymerase chain reaction (qRT‐PCR). Elastic moduli of skin and scar tissue were analyzed using a microstrain analyzer. Grafts contracted to ∼45% of their original size by day 14 and maintained their size. Grafting of GFP mouse skin onto wild‐type mice, and analysis of dermal thickness and hair follicle density, confirmed graft survival. Interestingly, hair follicles disappeared after grafting and regenerated in ear skin configuration by day 30. Radiological analysis revealed that panniculus carnosus doesn't contribute to contraction. Microscopic analyses showed that grafts show increase in cellularity. Granulation tissue formed after day 3. Collagen analysis revealed increases in collagen maturation over time. CD31 stain revealed increased vascularity. Macrophages and mast cells were increased. qRT‐PCR showed up‐regulation of transforming growth factor beta, alpha smooth muscle actin, and rho‐associated protein kinase 2 in HSc. Tensile testing revealed that human skin and scar tissues are tougher than mouse skin and scar tissues.